Marco Civil da Internet e serviços na nuvem: hermenêutica jurídica e tributação como indutores de inovação tecnológica - Gallindo, Sergio Paulo Gomes (2017)
Brazilian Law 12.965, 23 April 2014, referred to as The Internet Bill of Rights (Marco Civil da Internet in Brazil), represents an important landmark in Brazil´s legal system. Given its geographical reach, universality and its open environment, conducive to information haring and development of applications, the Internet has become an essential service to citizens, to governments and to the business, transcending national borders. As The Internet Bill of Rights starts producing effects within Brazilian legal environment and upon social actors operating in such a complex ecosystem, there is a growing need to deepen the exegesis of the legal diploma. Traditionally, hardware is sold as merchandise in buy-and-sell transactions concluded perfected by the equipment delivery. Software as commercialized as perpetual right of use license. In both cases, the commercial model is usually based in non-recurring prices, and the purchase is accounted as asset subject to depreciation. Given the Internet expansion and the technology evolution, new business models have emerged around a certain concept, known in the market as Cloud Services. Such offerings make available processing capacity and software licenses, through the Internet, in accordance to the customer´s need, and paid on recurring charges based on the usage. This work presents considerations about interpretation applicable to Law 12.965/2014, undertaken on the basis of its own legal principles and on the weighting of colliding principles, focusing on Net Neutrality and investigates taxation regimes (tax incidence hypotheses) applicable to new information and communication technologies, taking into account the juridical nature of the solutions. Considerations hereto presented rely on Economic Law as backdrop, regarding, in particular, ways in which the State intervenes in the economy, especially using the inductive form.